2018
DOI: 10.1039/c7ta10884b
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of NH2-functionalized black phosphorene for the electrocatalytic hydrogen evolution reaction

Abstract: We report a facile solid exfoliation method to prepare NH2-functionalized few-layer black phosphorene for use as an electrocatalyst for the hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 60 publications
7
139
0
1
Order By: Relevance
“…It can be observed that the three Raman peaks of the BP‐PZN nanosheets red shift slightly (about 2 cm −1 ) compared to those of the BP‐Bulk. These results give the further evidence that the thickness of nanolayer increases in BP nanosheets after coating with PZN polymer . Thermogravimetric analysis (TGA) was then conducted under nitrogen so as to confirm the mass loss process and formation of PZN in BP‐PZN.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…It can be observed that the three Raman peaks of the BP‐PZN nanosheets red shift slightly (about 2 cm −1 ) compared to those of the BP‐Bulk. These results give the further evidence that the thickness of nanolayer increases in BP nanosheets after coating with PZN polymer . Thermogravimetric analysis (TGA) was then conducted under nitrogen so as to confirm the mass loss process and formation of PZN in BP‐PZN.…”
Section: Resultsmentioning
confidence: 73%
“…Figure c,d presents the high‐resolution P2p and N1s XPS spectra of BP‐PZN. For P2p peaks of BP‐PZN, the spectrum can be deconvoluted into four peaks at 129.8, 130.6, 133.4, and 134.3 eV corresponding to P2p 3/2 and P2p 1/2 of PP bonds, PN, and PO bonds, respectively . Compared to BP‐Bulk, the P2p 3/2 and P2p 1/2 signals of BP‐PZN are slightly shift to lower binding energies, revealing an increase of electron concentration, a break of long‐range order, and the oxidation for surface P atoms of BP nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these above mentioned phosphide/BP, sulfide/BP, selenide/BP heterostructures and metal doped BP, non‐metal functionalizing BP is another effective way to design good potential electrocatalysts for HER. NH 2 ‐functionalized BP was prepared by using urea‐assisted ball milling to expose more dangling bonds and edges that favored charge transfer . CN‐group in Prussian blue with larger chemical electronegativity could passivate the edge and optimize the band structure of BP for HER .…”
Section: Bp Based Electrocatalysts For Hermentioning
confidence: 99%
“…The preferential migration of the active lone‐pairs protected BP against degradation, giving rise to excellent electrocatalytic stability, and outstanding OER performance (Figure b) with a low overpotential (310 mV at 10 mA cm −2 ), which can be competitive with commercial IrO 2 (297 mV) . Furthermore, BP‐Modified Co 3 O 4 as an efficient OER electrocatalyst was reported by our group . Particularly, two mixed valence states: Co 2+ and Co 3+ coexist in spinel Co 3 O 4 , and Co 2+ is identified as the catalytic active site, dominating the OER activity, while Co 3+ slows down the whole catalytic activity of Co 3 O 4 , which tends to bond with hydroxy groups .…”
Section: Bp Based Electrocatalysts For Oermentioning
confidence: 99%